Truss Morphometrics dan Hubungan Panjang Berat Moonfish Mene maculata Bloch & Schneider (1801) - Nurhayati, Defi; Sukmaningrum, Sri; Suryaningsih, Suhestri; Sugiharto, Sugiharto (Fakultas Biologi Universitas Jenderal Soedirman, 2023)
Mene maculata has high economic value and does not have sexual dimorphism. Therefore, in order for the population to be sustainable, information on the biology of male and female M. maculata fish is needed as a basis for management. The aim of the study was to determine the morphological performance, truss morphometrics, and lenght-weight relationship of male and female M. maculata. The research method is a survey and purposive random sampling in TPI PPS Cilacap. The observed variables were morphological performance, truss morphometrics and the lenght-weight relationship. The parameters measured are the truss distance in a ratio of the standard length. Truss morphometrics measured is the ratio between the truss distance of 15 points. Morphological performance was analyzed descriptively, truss morphometrics measurements were analyzed by t-test and the length-weight relationship was analyzed by correlation and regression tests. The results showed that morphological performance could not be used as a differentiator, while truss morphometrics could be used as a differentiator, namely at the base of the front of the anal fin to the base of the back of the anal fin, the male M. maculata was longer than the female. The results of the correlation test for the length and weight of male and female M. maculata both showed a closeness of 0.505 and 0.648; R values ​​for males 25.5% and females 42% and growth types of male and female M. maculata were allometric negative with b values ​​1.445 and 1.764.